Artificial Intelligence in Interpreting Education Curriculum: A Delphi Study for Interpreter Competencies - Yang, Chunwen; Jing Chen; Deyan Zou (Ilmu Inovasi Nusantara, 2025)
This study explores essential competencies for interpreters in the age of artificial intelligence (AI) to ensure they are well-equipped to navigate an evolving professional landscape. Using the Delphi method, a panel of experts identified and ranked key competencies necessary for interpreting graduates, ultimately classifying these into six primary dimensions: Core Cognitive Abilities, Lifelong Learning and Professional Development, Communication and Interpersonal Skills, Specialized Domain Knowledge and Linguistic Expertise, Ethics and Professionalism, and Technology and Information Management. The Technological Pedagogical Content Knowledge (TPACK) framework underpins the study, providing a structured approach to understanding the intersection of AI and interpreter competencies, emphasizing the need for critical thinking, adaptability, and ethical judgment. Findings indicate that competencies such as adaptability and critical thinking are vital for future interpreters, with implications for both curriculum development and professional training in interpreting education. Despite limitations in the diversity of expert perspectives, this study contributes valuable insights to interpreting education, highlighting areas for future research in refining competency frameworks and adapting curricula to AI-driven demands in interpreting